Landasan Psikologi Pendidikan Dalam Pembelajaran - Iis Yuliati; Cucu Atikah (Publikasi Indonesia, 2025)
The Role of Educational Psychology in Enhancing Learning and Instruction. This article explores the fundamental principles of educational psychology and its critical role in shaping effective learning environments. We examine core concepts such as student development, motivation, and effective learning strategies to highlight how an understanding of educational psychology can inform and improve pedagogical practices. Using a descriptive-analytical approach, this study finds that a solid grasp of educational psychology is essential for educators to design learning experiences that align with student characteristics. This ensures that educational goals are achieved optimally. This research contributes to the ongoing discussion on integrating psychological insights into educational frameworks to foster a more profound and successful learning process.